(untitled) (Journal of the College of Basic Education, 2026)
This research, entitled "The Rare Words in Abu al-’Ala’s Dictionary of Chapters and Ends," by Dr. Maytham Muhammad Ali, addresses an important linguistic phenomenon characteristic of several early works: the phenomenon of rare words, such as those found in Abu ’Ubaydah’s (d. 210 AH) "Gharib al-Qur’an" (Rare Words in the Qur’an), Ibn Qutaybah al-Dinawari’s (d. 276 AH), Ibn Qutaybah’s "Gharib al-Hadith" (Rare Words in Hadith), and Ubayd al-Qasim ibn Sallam’s "Al-Gharib al-Musannaf" (The Classified Rare Words), among others. This phenomenon is also present in Abu al-’Ala’s dictionary of chapters and ends. Because the book "Al-Fusul wa al-Ghayat" (Chapters and Ends) is considered a linguistic and intellectual encyclopedia in which multiple concepts intertwine, relying on diverse linguistic imagery that portrays humanity, animals, and nature in a profoundly symbolic way, Abu al-Ala’ used this unusual language as both an artistic and intellectual tool to express his existential vision, which is preoccupied with issues of death, annihilation, and the transience of the world. These are central themes that recur in most of his works, and they have been studied by critics and researchers, both past and present, who consider them among the most prominent features of his intellectual and literary project. Thus, Abu al-Ala’s lexicon of "Al-Fusul wa al-Ghayat" represents a linguistic and literary record that reflects al-Ma’arri’s conscious engagement with issues of word and meaning, and his critical approach to the richness and intricacies of the Arabic language. The author of the lexicon used this approach to explain its vocabulary. This research employs a descriptive-analytical approach, both lexicographical and semantic. It describes the phenomenon of rare words in Abu al-Ala’s lexicon, specifically in his book "Al-Fusul wa al-Ghayat" (Chapters and Ends). The study analyzes these rare words in terms of their morphological structure, linguistic composition, and contextual meaning, consulting Arabic dictionaries to determine their prevalence or unfamiliarity. Furthermore, the study seeks to elucidate Abu al-Ala’s methodology in presenting rare words and his purpose in highlighting their unfamiliarity to his contemporaries. The research concluded that Abu Al-Ala’s dictionary of chapters and goals contained strange words, which are not strange in their original linguistic form, nor in the records of old dictionaries, but rather are strange in a relative temporal sense, arising from the lack of use or neglect of the word in Al-Ma’arri’s era. It was found that these words are characterized by good composition, harmony of letters and ease of pronunciation on the tongue, which negates their verbal savagery, and makes their strangeness an incidental strangeness that disappears by learning their meaning. This indicates Al-Ma’arri’s awareness, and the author’s ability with his lexical choices and his reliance on words with deep roots in Al-Ma’arri’s language, as he re-employed them in new contexts that serve Al-Ma’arri’s intellectual and rhetorical purposes.